2021
DOI: 10.34238/tnu-jst.3945
|View full text |Cite
|
Sign up to set email alerts
|

Allometry Variation in Morphometrics of Glossogobius Sparsipapillus Caught Along Hau River, From Can Tho to Soc Trang Provinces

Abstract: Nghiên cứu này cung cấp dữ liệu về biến đổi đặc điểm hình thái của loài Glossogobius sparsipapillus ở Đồng bằng sông Cửu Long. Một tập hợp 355 cá thể, gồm 155 cá cái và 200 cá đực, được thu thập từ Cái Răng, tỉnh Cần Thơ và Long Phú, tỉnh Sóc Trăng từ tháng 1 đến tháng 12 năm 2020 để phân tích hình thái. Các phân tích thống kê cho thấy chiều dài tổng (TL) của cá có mối quan hệ chặt chẽ với chiều dài chuẩn (SL), chiều cao cơ thể (BH) và chiều dài đầu (HL) do các giá trị r2 cao của các phép hồi quy, ví dụ SL = a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the same distribution area as Mystus albolineatus in this study, Mystus mysticetus (Phan et al, 2022) also showed a significant difference in the TL-SL morphological relationship. This difference was not observed for Glossogobius sparsipapillus (Dinh et al, 2021a).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In the same distribution area as Mystus albolineatus in this study, Mystus mysticetus (Phan et al, 2022) also showed a significant difference in the TL-SL morphological relationship. This difference was not observed for Glossogobius sparsipapillus (Dinh et al, 2021a).…”
Section: Discussionmentioning
confidence: 58%
“…Due to the behavior and reproductive process, during development, there could be differences in growth rate among morphological characteristics of fish (Kim et al, 2008). In some species, this variation depended on the sex of the fish; for example, in Glossogobius sparsipapillus (Dinh et al, 2021a), males were more elongated than females, indicating that body length tends to grow stronger than the body height of the fish. In addition, in some other species of fish that have been studied, TL-SL relationships are also used to determine the sex of fish, such as Mystus mysticetus (Phan et al, 2022); Ellochelon vaigiensis (Nguyen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation